Editorial Vol12 no3 - Laura Steckley (Scottish Journal of Residential Child Care)
Welcome to the December 2013 issue of the Scottish Journal of Residential Child Care (SJRCC). This issue is going live a bit later than we had hoped (it is now February 2014), but the process of meeting a new aspiration often unfolds differently than planned. As Graham Connelly indicated in the June 2013 editorial, we have aspired to increase our output to three issues annually and we are pleased to have achieved this. This issue of the Journal marks some other changes as well. This is my first issue in the role of joint editor and it has been exciting to support the process of bringing it to publication. The issue holds a wider range of article style, allowing for a broader variety of voices to join the discussion about residential child care. This is another change for the journal, and I will offer a bit more about the articles themselves shortly.